The influence of breathing techniques on physical sport performance: a systematic review and meta-analysis - Laborde, S.; Zammit, N.; Iskra, M.; Mosley, E.; Borges, U.; Allen, M. S.; Javelle, F. (International Review of Sport and Exercise Psychology, 2024)
Breathing techniques are predicted to affect specific physical and psychological states, such as relaxation or activation, that might benefit physical sport performance (PSP). Techniques include slow-paced breathing (SPB), fast-paced breathing (FBP), voluntary hyperventilation (VH), breath-holding (BH), and alternate- and uni-nostril breathing. A systematic literature search of six electronic databases was conducted in April 2022. Participants included were athletes and exercisers. In total, 37 studies were eligible for inclusion in the systematic review, and 36 were included in the five meta-analyses. Random effects meta-analyses for each breathing technique were computed separately for short-term and longer-term interventions. Results showed that SPB and BH were related to improved PSP, with large and small effect sizes for longer-term interventions, respectively. In short-term interventions, SPB, BH, and VH were unrelated to PSP. There was some evidence of publication bias for SPB and BH longer-term interventions, and 41% of the studies were coded as having a high risk of bias. Due to an insufficient number of studies, meta-analyses were not computed for other breathing techniques. Based on the heterogeneity observed in the findings, further research is required to investigate potential moderators and develop standardised breathing technique protocols that might help optimise PSP outcomes.